TESTING OF POLYMER-COMPOSITE MATERIALS AFFECTED BY ELECTRIC LIGHTNING - Синеглазов, В. М.; Александрова, О. С. (Proceedings of National Aviation University (archive), 2021)
The method of testing the structural elements of aircraft made of polymer-composite materials and damaged by electric lightning for their further operation is considered. The result of the proposed technique is the assessment of residual mechanical stability and strength.